2017
DOI: 10.1186/s40560-017-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated respiratory infection in a resource-restricted setting: impact and etiology

Abstract: BackgroundVentilator-associated respiratory infection (VARI) is a significant problem in resource-restricted intensive care units (ICUs), but differences in casemix and etiology means VARI in resource-restricted ICUs may be different from that found in resource-rich units. Data from these settings are vital to plan preventative interventions and assess their cost-effectiveness, but few are available.MethodsWe conducted a prospective observational study in four Vietnamese ICUs to assess the incidence and impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 38 publications
2
36
0
1
Order By: Relevance
“…We did not distinguish between VAP and VAT as the pathogenesis and bacterial aetiology of the two entities are essentially the same and both are treated for a similar duration in Vietnam. A Vietnamese study analysing the costs of VAP and other VARI found little difference when similar patient groups were looked at [ 15 ]. All direct medical costs were estimated as the product of number of services and their unit cost.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not distinguish between VAP and VAT as the pathogenesis and bacterial aetiology of the two entities are essentially the same and both are treated for a similar duration in Vietnam. A Vietnamese study analysing the costs of VAP and other VARI found little difference when similar patient groups were looked at [ 15 ]. All direct medical costs were estimated as the product of number of services and their unit cost.…”
Section: Methodsmentioning
confidence: 99%
“…Because the antimicrobial therapy de-escalation rate was not reported in Vietnam, we varied this rate by the values from the prospective study of 24 intensive care units in Spain [ 22 ]. Varying the incidence density of VARI was performed with the additional analysis of data from a previous prospective observational study in 4 CCUs in Vietnam [ 15 ]. The extra duration of antimicrobial therapy was varied between 7–14 days to cover 2 common antimicrobials regimens of 7–8 days and 10–14 days [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical ventilation with an endotracheal tube has been identified as a primary risk factor for ventilator-associated pneumonia (VAP). 1,2 Despite current efforts to control VAP and hospital-acquired pneumonia, 3 even in patients who have not received mechanical ventilation, it remains a matter of concern. Many studies have focused on managing risk factors to prevent VAP and a few more recent publications have addressed the epidemiology of hospital-acquired pneumonia in subjects who were not mechanically ventilated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HAP occurs 48 hours or more after hospitalization and does not present on admission. For hospitalized patients, HAP can be divided into ventilator hospital-acquired pneumonia (V-HAP), in which pneumonia develops after endotracheal intubation over 48–72 hours, and nonventilator hospital-acquired pneumonia (NV-HAP) 7,8. A similar pathogenesis may exist in patients with burn injury.…”
Section: Introductionmentioning
confidence: 99%